Ambiguity in Supreme Court Decisions on Ambon's Customary Land: The 1814 Dati Register and the Challenge of Evidentiary Systems - Saija, Ronald; Pariela, Marselo Valentino Geovani; Demmatacco, Triska; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Ownership of recognized land in Ambon, particularly in the Dati (locally recognized land), is granted by the state to individuals who have rendered services to the state and possess strong legal rights that can be passed on to the rights holder's descendants. Generally, land in the Ambon region is customary land (tanah dati) subject to and controlled by the right of ownership (beschikkingsrecht) of the village or village concerned.Purposes of the Research: To examine the factors that led to the Supreme Court of the Republic of Indonesia's decisions being enforced using outdated evidence and how to influence the reconstruction of ambiguity regarding the justice of Supreme Court decisions enforced based on the 1814 Dati Register, which contains a failed evidentiary system.Methods of the Research: Sociolegal research, a combination of doctrinal and empirical legal research methods.Results Main Findings of the Research: The weaknesses of Supreme Court decisions enforced using outdated evidence are: The 1814 Dati Register was not intended as proof of land ownership under modern law, but rather as an administrative tool for colonial tax purposes; The 1814 Dati Register Letter is old, incomplete and often does not correspond to the actual conditions of existing customary land, thus causing uncertainty and disputes; the existence of differences in interpretation of customary law and national law in courts causes the decisions of the Supreme Court of the Republic of Indonesia often do not reflect substantive justice for indigenous peoples; and this failure has implications for obstacles to customary land registration at the National Land Agency and the potential for prolonged conflict between indigenous peoples and other parties, and the abolition of the dati institution as outlined in the decision on June 1, 1923, contains the meaning of changes in the customary land ownership system in Ambon, especially the change from the concept of dati-doesoen (land dati) to poesaka-doesoen. make it in academic English.